THE STATE AND DIRECTION OF SANSKRIT AND HINDI IN THE MUGHAL PERIOD - Karmasheel, Upendra Kumar; Sharma, Ram Ekwal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sanskrit was neglected during the period of the first two Mughal emperors, but the third Mughal emperor Akbar gave it royal patronage. Although there were 59 very important poets of different languages ​​in the court of Akbari, but the total number was much higher. Emperor Akbar also rewarded Sanskrit scholars. In that period, poets were mostly experts of both Sanskrit and Hindi. A dictionary of Sanskrit "Farsi Prakash" was written. Akbar ordered his court poet Faizi to convert important Sanskrit texts into Persian and explain its basic elements to the emperor. Faizi changed his name and came to Banaras and received Sanskrit education from the scholars there. After getting education, he revealed his secret to his teacher, he made it clear to the teacher that he was a Muslim. The teacher told him to translate whatever Sanskrit book he wanted but the teacher ordered him not to translate the Gayatri Mantra even by mistake. Faizi translated the important Sanskrit book ’Nal Damyanti’ into Persian and narrated it to the king. In this way, Faizi also translated some parts of Mahabharata. It should be noted that Persian was the official language in those times. In this way, we see that Sanskrit literature developed a lot. Ramayana, Atharvaveda, Panchtantra, Mahabharata, Bhaskar’s Ganit Shastra and Lilavati texts were translated into Persian. Faizi’s younger brother Abul Fazal also translated Kaliye Daman into Persian.